Promoting sustainable disposal behaviour of unused medicines: Exploring the barriers and drivers using the COM-B model - Joris Galama; Bianca Harms (Sustainable Futures)
Environmental pollution from improper medicine disposal is a growing concern. Proper disposal through returning unused medicines to pharmacies or recycling points can mitigate this issue. This study investigates disposal behaviours of medicine residues in The Netherlands, highlighting the reasons why people possess unused medicines, current disposal behaviours and the experienced barriers and drivers of correct medicine residue disposal behaviour by applying the capability, opportunity, motivation, and behaviour (COM-B) model. Surveying 602 respondents online, we found that medication type (solid vs liquid), age, and education level significantly influence disposal methods. Age emerged as a positive predictor of correct disposal behaviour. Gender, however, showed no significant effect. Interestingly, individuals with a middle level of education exhibit a greater likelihood of engaging in correct disposal behaviour compared to those with a high education level. No significant differences were found between respondents with a low and middle education level, or between respondents with a low and high education level. Furthermore, the findings highlight the explanatory and added value of applying the COM-B model in this context. Specifically, psychological capability and physical opportunity were significant positive predictors of correct disposal behaviour, whereas social opportunity, reflective motivation, and automatic motivation did not show significant predictive value. These findings offer valuable insights for developing interventions that contribute to correct disposal practices.